Consumer Behavior Analysis In Purchasing Decisions Of Yamaha Motorcycles At Jaya Perkasa Motor Sumedang - ila Karmila (SINTESA, 2023)
Public demand for motorcycles is always increasing. The motorcycle automotive manufacturers compete with each other to offer their products. Yamaha is one of the biggest and best automotive companies, especially in Indonesia. In the current uncertain economic situation as a result of the Covid 19 pandemic crisis which has resulted in a sluggishness in motorcycle sales which has had an impact on the motorcycle sales marketing process. So before marketing their products, companies need to pay attention to consumer behavior first. Because consumer behavior will be the target for purchasing products that will be marketed. The purpose of this research is to analyze consumer behavior in determining the purchase of a Yamaha motorcycle at Jaya Perkasa Motor Sumedang. This study uses qualitative methods with a descriptive approach and belongs to field research with semi-structured interviews and documentation as data collection techniques. The findings from this study are that prospective motorcycle consumers in buying a motorbike have many considerations to get the motorbike they want, such as what are the advantages, affordable prices, if purchased on credit with low interest and how long does the delivery process take because the current process is through ordering goods first or indent for 1 month to 3 months to purchase a motorcycle unit